Development of an Integrated Coaching System for Health Promotion in Early Childhood at Child Development Centers - Phattarasatjatum, Preeyada (Journal of Research and Curriculum Development, 2022)
The purposes of this research and development are as follows: (1) to develop and seek an efficient integrated coaching system for health promotion in early childhood at child development centers; and (2) to evaluate the effectiveness of an integrated coaching system for health promotion in early childhood at child development centers by using embedded and mixed methods research with a sample of 40 children in early childhood at childcare centers. The research instruments were a form of integrated coaching system and an early childhood health promotion assessment. The data was analyzed using mean, standard deviation, a dependent t-test, a growth score, a repeated measures ANOVA and content analysis. The results indicated the following: (1) the integrated coaching system consisted of three elements: (1.1) upstream; (1.2) midstream, which indicated the 5P’s Model, in which the first P was Purpose, the second P was Participation, the third P was Procedure Design, the fourth P was Practice, and the fifth P was Performance Reflection; and (1.3) downstream, which was developed and obtained an E1/E2 efficiency value of 82.50/87.50; and (2) the level of effectiveness after using the integrated coaching system revealed the following: (2.1) the average score for early childhood health was higher (p<.05), and (2.2) early childhood health development had a higher growth score (p<.05). This research was utilized for health promotion in early childhood at child development centers. As a result, those in early childhood had better health and an improved quality of life.